Successful Delivery After Myomectomy for Spontaneous Ruptured Pyomyoma: A Case Report and Literature Review - Yang Pan; Jue Li; Qian Zhou; Yi Yu; Juntao Liu; Jinsong Gao; Yijun Song; Yin Sun; Qi Guo (Maternal-Fetal Medicine)
Abstract. In this article, we report a case of spontaneous ruptured pyomyoma during pregnancy with successful delivery after myomectomy. A 35-year-old pregnant female (27 weeks of gestation) presented with lower abdominal pain. The patient had a history of uterine fibroids. Ultrasound, computed tomography, and magnetic resonance imaging confirmed a spontaneous ruptured pyomyoma (maximum diameter: 12.6 cm). Myomectomy was performed, and her abdominal distension and pain were significantly improved within 1 day; the condition of the fetus was normal. One month after surgery, severe tenderness was detected in the lower right side of the uterus. Considering the higher risk of uterine rupture and associated complications, a cesarean section was performed. The mother and neonate were discharged 3 and 42 days after delivery, respectively, in good condition. Myomectomy for spontaneous ruptured pyomyoma during pregnancy may be feasible and extend gestational age to improve outcomes for the mother and neonate.